PROGNOSTIC VALUE OF PATHOLOGIC Q-WAVE AND TIME OF ITS APPEARANCE IN PATIENTS WITH MYOCARDIAL INFARCTION: COMPARISON STUDY - V. A. Shulman; S. E. Golovenkin; V. N. Simulin; V. V. Radionov; G. V. Matyushin (Рациональная фармакотерапия в кардиологии)
Aim. To evaluate short- and long-term prognosis of myocardial infarction (MI) depending on occurrence of pathologic Q-wave on ECG and time of its appearance.Material and methods. 616 patients with initial ST-elevated MI were included into the study — 254 women and 362 men, aged 62.1±11.2. All patients were split up three groups depending on occurrence of pathologic Q-wave on ECG and time of its appearance. First group consisted of 311 patients with early Q-wave (during first 6 hours from onset of MI symptoms). Second group consisted of 120 patients with late Q-wave (from 6 to 24 hours from onset of MI symptoms). Third group consisted of 185 patients with non-Q-wave MI.Results. The hospital lethality in the patients with early Q-wave was significantly higher than this in patients of the second and the third groups. However, we didn’t reveal significant differences between patients with late Q-wave and patients without Q-wave on ECG. The incidences of cardiac death (sudden death and fatal MI), non-fatal MI and hospitalization because of unstable angina was assessed during next two years. During the follow-up period patients of three groups had similar incidences of the non-fatal MI and hospitalization because of unstable angina. However, incidence of cardiac death was significantly higher in early Q-wave group in comparison with non-Q-wave group.Conclusion. Occurrence of pathologic Q-wave on ECG and time of its appearance should be taken into account to assessed short- and long-term prognosis of MI.